Constructive conversations on resilient urban futures - Heinonen Sirkka; Karjalainen Joni; Taylor Amos; Rashidfarokhi Anahita; Toivonen Saija; Tähtinen Lassi (Turun yliopisto. Turun kauppakorkeakoulu, 2025)
This publication is a co-created compilation of various conversations concerning our possibilities and pathways towards resilient urban futures. A series of interviews conducted so far within the Real Estate and Sustainable Crisis Management in Urban Environments (RESCUE) project on several occasions – such as conferences, research visit – have been documented here to give food for thinking and discussions concerning resilience. The questions of the interviews have been tailor-made to address the expertise of each interviewee, while the core of interviews touches upon the topic of urban resilience in its all dimensions as well as the issues of forward-looking thinking and action.
Another type of anticipatory method, as a conversational tool we wish to experiment with, is a narrative. The researchers of the RESCUE project chose an actual case area for reviewing its crisis resilience as well as potential for wellbeing of its residents and the preservation of the environment. The related conversations were used to construct a narrative of the area in 2050 and test an imagined pathway towards resilience. The narrative is a work in progress – meant to be used for reflections, elaborations, discussions and further narratives among its readers, stakeholders to the area and the topic at hand as well those interested in designing and constructing resilient urban futures.